Komunikasi Pemasaran Terpadu Mata Najwa On Stage 2016 Dalam Meningkatkan Jumlah Khalayak (Studi Pada Activation & Media Mix Department Metro TV Jakarta) - Handayani, Mery; Purnawan, Ni Luh Ramaswati; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium; Vol 1 No 2 (2018), 2018)
ABSTRACT Mata Najwa is one of favourite talk show programme of Metro TV. Beside on air program, Mata Najwa also have an off air program called Mata Najwa On Stage. The purpose of this research is to know the implementation of Integrated Marketing Communication in increasing the audience on Mata Najwa On Stage 2016. In this case, activation & media mix department is the one who coordinated the whole program. This research is a qualitative research with qualitative descriptive methods. Analytic technique that is use in this research is Miles and Huberman Interactive Analysis Technique. The result of this research show that activation & media mix department Metro TV Jakarta already implemented Integrated Marketing Communication in increasing the number of audience, however not all of the elements were used. From six of Shimp and Andrew Integrated Marketing Communication concepts, only three have been used on Mata Najwa On Stage 2016 . Keywords : Komunikasi Pemasaran Terpadu, Mata Najwa On Stage, Metro TV Jakarta